The formal education journey of Cassim Dangor, 1963-1985 : reflections on education challenges in apartheid South Africa (Historia, 2021)
Most students who attended the University College, Durban, which was established on Salisbury Island in 1961, were pioneers in two important senses: they were amongst the first to attend a racially exclusive university for Indians, as well being first generation students. Both scenarios presented challenges. This article focuses on the experiences of the Transvaal-born Cassim Dangor who, as an "Indian", faced many restrictive segregationist policies in his attempts to acquire tertiary education. While apartheid is often portrayed as a totalising institution, and despite the fact that individual stories can be esoteric, anecdotal and unrepresentative, a life history methodology provides a means to examine how individuals understood apartheid; how they were affected by it; the ways in which they attempted to make sense of their lives; and how they sought spaces in the system. The article also charts the growth of Pharmacy as a discipline at the university.  Die formele opvoedings reis van Cassim Dangor, 1963-1985 : refleksies rakende opvoedings uitdagings in apartheid Suid-Afrika Die meeste studente wat die Universiteits Kollege, Durban, wat in 1961 geskep is, bygewoon het was pioniers op twee belangrike wyses: hulle was die eerstes wat aan 'n universiteit wat eksklusief vir Indiërs geskep gestudeer het en hulle was ook die eerste geslag universiteits studente. Beide die scenarios het uitdagings geoffer. Die artikel fokus op die ervaringe van die Transvaals gebore Cassim Dangor wie, as 'n Indier, vele beperkende apartheids wetgewings beleef het in sy strewe na tersiêre onderwys. Hoewel apartheid gereeld voorgehou word as 'n totaliserênde instelling, en ongeag die feit dat sommige stories esoteries, eensydig en onverteenwoordigend kan wees, laat 'n lewensgeskiedenis metodologie 'n eksaminering toe van hoe enkelinge apartheid ervaar het, hul daardeur beinvloed is, hoe hulle probeer sin maak het van die stelsel en hoe hulle hul plek daarin gesoek het. Die artikel karteer oof die ontwikkeling van Farmasie as 'n vakgebied aan die universiteit.
Keywords: Apartheid; Salisbury Eiland; University of Durban-Westville; Pharmacy (as an academic discipline)